Overview of the use of clean cookstoves in the Brazilian semiarid region - Mazorra, Javier; da Costa Barreto, Renata; Ferreira dos Santos, Paula; Suárez Bonet, María; de la Sota, Candela; Checco, Guilherme; Almeida, Fabio; Tadeu Assad, Luís (Sustainability in Debate, 2019)
Wood cookstoves are common in the Brazilian semiarid region. Most families use traditional versions, which have a series of social, environmental and health-related impacts. “Improved cookstoves” refer to cleaner and more efficient cookstoves. These include adaptations that improve energy efficiency and reduce indoor air pollution, bringing benefits such as the reduction of firewood consumption for cooking, reduction of the emission of polluting gases originating from firewood burning and fewer health impacts, also contributing to forest conservation. Although the improved cookstoves sector is still relatively underdeveloped in the Brazilian semiarid region, in recent years interest in these technological alternatives has increased. In this context, the present study contributes to the compilation and organization of information referring to the use of improved cookstoves in the Brazilian semiarid region.